2012
DOI: 10.5172/jmo.2012.18.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Are financing decisions of family-owned SMEs different? Empirical evidence using panel data

Abstract: This paper analyses if ownership structure is an important determinant of capital structure decisions, on the basis of two sub-samples of family-owned and non-family owned SMEs, and using panel data models. The results suggest that family ownership is an important determinant for: i) the variations of short and long-term debt stimulated by financial deficit; ii) the speed of adjustment of short and long-term debt towards the respective target levels; and iii) the relationships between determinants and short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Nevertheless, the GMM system estimator can only be considered if the restrictions (a consequence of using instruments) are valid and there is no second-order correlation. To test the null hypothesis of validity of instruments we use the Hansen test and to evaluate the null hypothesis of absence of second-order correlation we utilize the Arellano-Bond test for AR(2), like Kowalewski, Talavera, andStetsyuk (2009), Serrasqueiro, Nunes, andda Silva (2012), and Connelly et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the GMM system estimator can only be considered if the restrictions (a consequence of using instruments) are valid and there is no second-order correlation. To test the null hypothesis of validity of instruments we use the Hansen test and to evaluate the null hypothesis of absence of second-order correlation we utilize the Arellano-Bond test for AR(2), like Kowalewski, Talavera, andStetsyuk (2009), Serrasqueiro, Nunes, andda Silva (2012), and Connelly et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Families are providers of ''patient capital'' (Lumpkin and Brigham 2011), and can contribute with personal assets to support the business (Serrasqueiro, Nunes, and da Silva 2012). Family firms may be anticipated to be less leveraged than nonfamily firms as high debt levels may jeopardize a large portion of family financial and human capital attached to the firm (Mishra and McConaughy 1999).…”
Section: The Effects Of Family and Lone Founder Involvement On Leveragementioning
confidence: 99%
“…The SMEs are found to rationally adjust to the optimal target ratio (Aybar-Arias et al , 2012). With regard to family control’s impact on the SMEs’ financial decisions towards reaching the target leverage, Serrasqueiro et al (2012) asserted that the costs could obstruct the adjustment process. Reasoning this obstruction, Serrasqueiro et al (2022) found that the SMEs stay away from the target ratio for a longer duration when faced with the cost of deviation or insolvency cost higher than the cost of adjustment or transaction cost.…”
Section: Resultsmentioning
confidence: 99%
“…This has a fundamental and ongoing input into "what businesses small businesses are in". Clearly, the results of interviews suggest that there is a huge gap between academic reasoning (e.g., Serrasqueiro et al, 2012;Irwin & Scott, 2010;Beck et al, 2008) and real practice with the importance of financial risk.…”
Section: Interview Resultsmentioning
confidence: 99%